(untitled) (Global Journal of Medical Research, 2023)
Methionine adenosyltransferase (MAT) deficiency is a rare inherited disorder of methionine metabolism that can lead to a wide range of symptoms, including jaundice, bleeding episodes, and neurological impairment. We report the case of an 8-month-old female infant, who presented with yellowish discoloration of skin, distended abdomen, and bleeding episodes. On further evaluation, she was found to have high levels of methionine in her blood. A diagnosis of MAT deficiency was made, and was started on appropriate treatment with a methioninerestricted diet and supplements.